2012
DOI: 10.1021/nl203033h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in Dopant-Free ZnO Nanoplates

Abstract: It is known that bulk ZnO is a nonmagnetic material. However, the electronic band structure of ZnO is severely distorted when the ZnO is in the shape of a very thin plate with its dimension along the c-axis reduced to a few nanometers while keeping the bulk scale sizes in the other two dimensions. We found that the chemically synthesized ZnO nanoplates exhibit magnetism even at room temperature. First-principles calculations show a growing asymmetry in the spin distribution within the distorted bands formed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…and/or intrinsic room-temperature ferromagnetism in these materials is not yet fully understood. [7][8][9] Venkatesan et al 6 have observed d 0 magnetism in HfO 2 thin lms and have triggered extensive experimental activities in the eld of the room-temperature ferromagnetism of many semiconductors and nanomaterials. 6 In recent years, the d 0 magnetism of nanomaterials has been considered to be one of the most interesting and challenging phenomena that may provide an avenue for investigating and understanding the origin of nanomagnetism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and/or intrinsic room-temperature ferromagnetism in these materials is not yet fully understood. [7][8][9] Venkatesan et al 6 have observed d 0 magnetism in HfO 2 thin lms and have triggered extensive experimental activities in the eld of the room-temperature ferromagnetism of many semiconductors and nanomaterials. 6 In recent years, the d 0 magnetism of nanomaterials has been considered to be one of the most interesting and challenging phenomena that may provide an avenue for investigating and understanding the origin of nanomagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent years, the d 0 magnetism of nanomaterials has been considered to be one of the most interesting and challenging phenomena that may provide an avenue for investigating and understanding the origin of nanomagnetism. [7][8][9] Surface-capping molecules, 7,15 defects and/or vacancies 6,10 are considered to be very important causes for d 0 magnetism in ZnO nanostructures and thin lms. Magnetism has been reported in various nonmagnetic oxides, 6,10 selenides 11,12 and Au-metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to design new pigment materials with desirable properties, however, requires a deep theoretical understanding of the underlying physical processes that involve the interaction of light with crystalline materials. The development of computational methods, particularly plane‐wave electronic structure calculations, coupled with constantly increasing available computer power have allowed researchers to study solid‐state phenomena responsible for a variety of applications, particularly in the areas of semiconducting materials, organic photovoltaics, solid electrolytes, lithium‐ion batteries, magnetic materials, surface chemistry, and catalysis . The situation with pigments, however, is different: many commercially important materials are used without any detailed understanding of the structural features responsible for their optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the suitable morphologies, chemistry stability, low electron affinity [4], a variety of 1-D ZnO nanostructures, such as nanopins [5], nanorods [6], nanaotubes, [7] nanowires [8], [9] and 2-D ZnO nanosheets, nanodiscs and nanoplates [10]- [12] have been fabricated. Various synthetic methods such as chemical vapor deposition [13], hydrothermal method [14], pulsed laser deposition [15], furnace [16], electrochemical deposition [17] and electron-beam lithography [18] have been developed for the fabrication of ZnO nanostructures with various geometrical morphologies.…”
Section: Introductionmentioning
confidence: 99%